2020
DOI: 10.21037/jtd.2020.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Current issues in transcatheter aortic valve replacement

Abstract: Background: aortic stenosisAortic stenosis (AS) is one of the most common forms of valvular disease in Western countries (1-3). It shows a consistent association with age, with prevalence ranging from 0.2% in the 50-59-year group to 9.8% in the 80-89-year cohort (4). Its prevalence is expected to increase due to higher life expectancy and population aging (5,6). It is also the most common reason for heart valve replacement (7).In a recent editorial paper (8), Eugene Braunwald put in perspective the medical adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 135 publications
2
20
0
1
Order By: Relevance
“…[ 21 , 22 ]. Complications of new PPM implantation were similar in recent low-risk TAVR trials to the those in the previous studies in higher-risk patients [ 54 ]. The Evolut Low-Risk TAVR Trial with self-expanding valves also showed that significantly more low-risk TAVR patients underwent postoperative permanent pacemaker (PPM) implantation than SAVR patients (17.4% vs. 6.1%, respectively) [ 18 ].…”
Section: Challenges Facing Tavr In Low-risk Patientssupporting
confidence: 73%
See 3 more Smart Citations
“…[ 21 , 22 ]. Complications of new PPM implantation were similar in recent low-risk TAVR trials to the those in the previous studies in higher-risk patients [ 54 ]. The Evolut Low-Risk TAVR Trial with self-expanding valves also showed that significantly more low-risk TAVR patients underwent postoperative permanent pacemaker (PPM) implantation than SAVR patients (17.4% vs. 6.1%, respectively) [ 18 ].…”
Section: Challenges Facing Tavr In Low-risk Patientssupporting
confidence: 73%
“…Balloon-expandable THV are associated with a lower risk of PPM implantation than self-expanding valves [ 37 , 53 , 55 , 56 ]. This is felt to be due to the increased radial force on the LVOT by self-expanding valves [ 54 ]. For example, an average of 25.8% of TAVR cases with the self-expanding CoreValve is associated with new PPM, while the average rates in TAVR with balloon-expanding SAPIEN valve are much lower at 6.5% [ 53 ].…”
Section: Challenges Facing Tavr In Low-risk Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aortic stenosis remains the most common heart valve disease with a poor prognosis if not treated. Trans-catheter aortic valve replacement (TAVR) has dramatically improved prognosis in selected patients with severe aortic stenosis, particularly in those not eligible for surgical replacement ( 9 ). Certain prognostic biomarkers (including those reflecting anemia, renal dysfunction, and malnutrition) ( 10 13 ) have been shown to be associated to lower survival rates.…”
Section: Introductionmentioning
confidence: 99%